2016
DOI: 10.1186/s13756-016-0121-8
|View full text |Cite
|
Sign up to set email alerts
|

Re-emergence of the susceptibility of the Salmonella spp. isolated from blood samples to conventional first line antibiotics

Abstract: BackgroundEnteric fever is an important public health problem in Nepal. Due to emergence of multidrug resistant strains of Salmonella spp. the conventional first-line drugs, ampicillin, chloramphenicol, and cotrimoxazole have not been used as empiric therapy for treatment of enteric fever for last two decades and there have been increased uses of fluoroquinolones as the drugs of choice. The aim of this study was to evaluate and analyze the antimicrobial susceptibility patterns of Salmonella spp.MethodsA total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 24 publications
9
62
3
Order By: Relevance
“…This demonstrates that ST and SPA are fully susceptible to ceftriaxone. These results are consistent with other studies from Nepal which have shown full susceptibility to ceftriaxone [14][15][16] . An important implication of these fi ndings is that ceftriaxone is a very good choice for empirical treatment of suspected enteric fever.…”
Section: Ceftriaxonesupporting
confidence: 83%
See 2 more Smart Citations
“…This demonstrates that ST and SPA are fully susceptible to ceftriaxone. These results are consistent with other studies from Nepal which have shown full susceptibility to ceftriaxone [14][15][16] . An important implication of these fi ndings is that ceftriaxone is a very good choice for empirical treatment of suspected enteric fever.…”
Section: Ceftriaxonesupporting
confidence: 83%
“…They found three isolates of ESBL producing SPA. In contrast to these studies, full susceptibility of isolates to cefotaxime has been documented by Shrestha et al 16 . As ESBL gene is mobile in nature, the mechanism of resistance in ST and SPA may be due to horizontal transfer of ESBL gene.…”
Section: Cefotaximementioning
confidence: 56%
See 1 more Smart Citation
“…So Salmonella typhi infections are getting controlled and Salmonella paratyphi A is emerging (Bharmoria and BehariVaish, 2016 Increased use of second line anti-salmonellae drugs and the discontinuation of use of the conventional first line antimicrobial agents for the treatment of the enteric fever for last two decades, probably have led to the reemergence of susceptibility to first line antibiotics. As plasmids are responsible for determining resistance to these first line antibiotics; loss of these resistance determining plasmids, may be the reason for the re-emergence of the sensitive strains (Chand et al, 2014;Shrestha et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Nalidixic acid (NAL), ampicillin (AMP), tetracycline (TCY), sulfamethoxazole-trimethoprim (SXT), and chloramphenicol (CHL) used to treat invasive Salmonella infection in the 1970s and 1980s are referred to as conventional first-line antibiotics [4]. Third-generation cephalosporins and fluoroquinolones became primary antibiotics in recent years [5].…”
Section: Introductionmentioning
confidence: 99%